The Effectiveness of The Let’s Read Application on Students’ Reading Comprehension of Narrative Text - Ardianti, Sheila Dwiclaudia; Yuliana, Yohanes Gatot Sutapa; Wardah, Wardah (Universitas Muhammadiyah Barru, 2026)
The Let’s Read application was investigated to evaluate its effectiveness on students’ ability to comprehend narrative passages. This research utilizes the pre-experimental approach, involving a one-group design that involved testing participants both prior to and following the intervention. There were 30 students as participants from class VIII A at SMP N 24 Pontianak during the 2023/2024 academic year, selected through cluster sampling. The data were gathered using measurement techniques, with tests used as the research instrument. The results revealed that the Let’s Read application helps students comprehend narrative text. The treatments affected the post-test average (79,75), which was higher than the pre-test average (61,17). A t-test analysis produced a score of 12.55, which exceeded the critical value of 1.699 with 29 degrees of freedom and a 0.05 alpha level. This finding contradicted the initial hypothesis and confirmed the researcher's alternative hypothesis. In addition, the calculated effect size was 2.174, indicating a strong impact, as it was beyond the 0.5 range of effect sizes. Therefore, the study concludes that the implementation of Let’s Read as an alternative media was effective in helping students comprehend the narrative text.